2001
DOI: 10.1074/jbc.m103111200
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Regulation of Plant Succinate Dehydrogenase

Abstract: Regulation of succinate dehydrogenase was investigated using tightly coupled potato tuber mitochondria in a novel fashion by simultaneously measuring the oxygen uptake rate and the ubiquinone (Q) reduction level. We found that the activation level of the enzyme is unambiguously reflected by the kinetic dependence of the succinate oxidation rate upon the Q-redox poise. Kinetic results indicated that succinate dehydrogenase is activated by both ATP (K ½ ϳ 3 M) and ADP. The carboxyatractyloside insensitivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…SDH, also often referred to as complex II, has a dual function, being important in both the TCA cycle and the aerobic respiratory chain, through the catalysis of the oxidation of succinate to fumarate and the reduction of ubiquinone to ubiquinol, respectively (Affourtit et al 2001; Araújo, Nunes-Nesi, et al 2011). The conserved elements of this complex, a mere four polypeptides, comprise two peripheral membrane proteins—a flavoprotein (SDH1), and an iron-sulfur binding protein (SDH2)—as well as two integral membrane proteins (SDH3 and SDH4) (Rasmusson et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…SDH, also often referred to as complex II, has a dual function, being important in both the TCA cycle and the aerobic respiratory chain, through the catalysis of the oxidation of succinate to fumarate and the reduction of ubiquinone to ubiquinol, respectively (Affourtit et al 2001; Araújo, Nunes-Nesi, et al 2011). The conserved elements of this complex, a mere four polypeptides, comprise two peripheral membrane proteins—a flavoprotein (SDH1), and an iron-sulfur binding protein (SDH2)—as well as two integral membrane proteins (SDH3 and SDH4) (Rasmusson et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that the activation state level of the enzyme is unambiguously reflected in the kinetic dependence of the succinate oxidation rate on the ubiquinone redox poise. Kinetic results indicated that it is additionally activated by both ATP and ADP (2).…”
Section: Mitochondrial Contribution To Energy Metabolism-respirationmentioning
confidence: 92%
“…The latter is detoxified and recycled back to 3PGA via photorespiration, a complex energy consuming pathway that liberates fixed carbon and nitrogen as CO 2 and NH 4 + , respectively (31). Moreover, the photorespiratory cycle is a highly compartmentalized process with enzymatic reactions occurring across four compartments.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, plant mitoK ATP appears to play a major role in the in vitro regulation of succinate dehydrogenase (SDH). Affourtit et al [24] showed that SDH is inactivated by K + and reactivated by low concentrations of nucleotides acting from the intermembrane space, and hypothesized that these effects are mediated via plant mitoK ATP .…”
Section: Discussionmentioning
confidence: 99%